2010
DOI: 10.1017/s0022149x10000283
|View full text |Cite
|
Sign up to set email alerts
|

The mucosal response of hamsters to a low-intensity superimposed secondary infection with the hookworm Ancylostoma ceylanicum

Abstract: An experiment was conducted to assess the mucosal response to low-dose superimposed challenge with Ancylostoma ceylanicum. Hamsters were assigned to five treatment groups (1-5 respectively): naïve controls; primary immunizing infection controls; challenge controls; immunized, anthelmintic-treated, challenged group; immunized, superimposed challenge group. Group 4 hamsters were resistant to challenge, whereas most of the challenge inoculum larvae established in Group 5. Villus height and crypt depth measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
(108 reference statements)
2
4
0
Order By: Relevance
“…This concurs with the results of a challenge experiment in which much higher eosinophil levels were recorded on days 10 and 31 after infection, reaching in excess of 500 eosinophils/mm 2 , compared with days 73 and 94, by which time the eosinophil response had declined to levels of between 200 and 300 cells/mm 2 (Alkazmi & Behnke, 2010), a pattern that is not dissimilar to that observed here. A very similar pattern was reported also by Alkazmi & Behnke (2011) in another challenge experiment, so quite clearly the intense levels of eosinophil infiltration observed early during primary exposure, reaching in excess of 600 cells/mm 2 , fall with time in these chronic infections. The marked contrast, then, with repeatedly infected animals, where eosinophil levels stayed elevated, at over 700 cells/mm 2 even 10 weeks after the first dose of larvae, may reflect a response to the continued stimulation of the mucosa by the arrival of fresh larvae.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This concurs with the results of a challenge experiment in which much higher eosinophil levels were recorded on days 10 and 31 after infection, reaching in excess of 500 eosinophils/mm 2 , compared with days 73 and 94, by which time the eosinophil response had declined to levels of between 200 and 300 cells/mm 2 (Alkazmi & Behnke, 2010), a pattern that is not dissimilar to that observed here. A very similar pattern was reported also by Alkazmi & Behnke (2011) in another challenge experiment, so quite clearly the intense levels of eosinophil infiltration observed early during primary exposure, reaching in excess of 600 cells/mm 2 , fall with time in these chronic infections. The marked contrast, then, with repeatedly infected animals, where eosinophil levels stayed elevated, at over 700 cells/mm 2 even 10 weeks after the first dose of larvae, may reflect a response to the continued stimulation of the mucosa by the arrival of fresh larvae.…”
Section: Discussionsupporting
confidence: 88%
“…Second, a consistent finding of our experiments with A. ceylanicum in hamsters has been the decline in Paneth cells after single-pulse infections (Elphick & Mahida, 2005; Alkazmi et al , 2008; Alkazmi & Behnke, 2010, 2011). We found that after clearance of worms, and also after subsequent challenge infection, there was a marked rebound effect, with Paneth cell numbers reaching much higher levels than in naïve controls, and this coincided with loss of incoming larvae in the first 2 weeks of the challenge infection (Alkazmi et al , 2008; Alkazmi & Behnke, 2010).…”
Section: Discussionsupporting
confidence: 80%
“…Despite of these intense changes, some adult worms survive for lengthy periods of time in this abnormal, inflamed environment in both primary and challenge infections in hamsters. At the same time, hamsters are capable to sustain and tolerate these intestinal alterations and mucosal inflammatory response for several weeks and, after removal of the adult worms, rapidly bounce back to normal [105].…”
Section: The Role Of Il-4 Il-13 and Aams In Infections By Helminth mentioning
confidence: 97%
“…Currently, there is limited information regarding stem cell responses during distinct stages (initiation, progression, repair and resolution) of inflammatory responses. There is also significant interest in the role of Paneth cells in the pathogenesis of chronic inflammatory diseases such as Crohn's disease (11) and in chronic nematode infections such as those caused by human hookworms (12,13).…”
Section: Introductionmentioning
confidence: 99%